STRUCTURE AND CLINICAL EVALUATION OF PERIODONTAL DISEASES IN DRUG ADDICT PATIENTS - Федун, И.Р.; Zubachik, V.М. (World of Medicine and Biology, 2018)
Abstract. There are reports of the influence of narcotic drugs on cardiovascular, digestive, CNS, immune systems, but the dental status of this category of patients in not described enough. Condition of tissues and organs of the oral cavity of addict persons are studied insufficiently. Aim. To investigate the structure and peculiarities of the development of periodontal tissue pathology in drug addicted patients.Material and Methods. The article describes the results of the study of the state of periodontal tissues in 105 drug addicts, which include clinical observations and index assessment (OНI-S, PMA, PI), taking into account the duration of drug use and 55 non-drug addicts with periodontal pathology (gingivitis, generalized periodontitis). Results. Drug-dependent patients who were actively taking drugs were badly cooperative and usually did not respond to the doctor's questions, while individuals with defined withdrawal syndrome demonstrated apathy and drowsiness. Data from a clinical study of drug addicts patients show that gingivitis was detected in 15.2 % (16/105), initial - Іst degree of generalized periodontitis (GP) – 26.7 % (28/105), IInd degree of GP – 30.5 % (32/105), IIIrd degree of GP – 27.59 % (29/105). The statistically significant difference between the results of the index evaluation (OНI-S, PMA, PI) of periodontal tissues of drug addicts and non-addicted patients was determined and probably indicates the negative impact of narcotic drugs on the periodontal status of patients with drug addiction. It was found characteristic inflammatory diseases of the periodontal tissues in the groups of drug addicts with experience of abuse up to 5 and 6-10 years. These groups consisted mainly of young people. Іn drug addicted patients with 11-15 years of experience, the most severely diagnosed GP of IInd degree – 14.3% (15/105) and patients with experience of 16-20 years were most often suffered from GP of ІІІrd degree – 13.3% (14/105).Conclusion. In drug addicts, complaints did not always match the clinical picture, which make difficult the correct diagnosis of diseases of the oral cavity, especially of periodontal tissues. Тhe progression of pathological processes in the periodontal tissues of drug addicts related to the term of drug use.
Keywords: gingivitis; periodontitis; drug abuse; clinical studies